Study on Large Deformation Behavior of Polyacrylamide Hydrogel Using Dissipative Particle Dynamics - Lei, Jincheng; Xu, Shuai; Li, Ziqian; Liu, Zishun (Frontiers in Chemistry, 2020)
Meso-scale models for hydrogels are crucial to bridge the conformation change of polymer chains in micro-scale to the bulk deformation of hydrogel in macro-scale. In this study, we construct coarse-grain bead-spring models for polyacrylamide (PAAm) hydrogel and investigate the large deformation behavior and fracture behavior by using Dissipative Particle Dynamics (DPD) to simulate the crosslinking process. The crosslinking simulations show that sufficiently large diffusion length of polymer beads is necessary for the formation of effective polymer. The constructed models show the reproducible realistic structure of PAAm hydrogel network, predict the reasonable crosslinking limit of water content and prove to be sufficiently large for statistical averaging. Incompressible uniaxial tension tests are performed in three different loading rates. From the nominal stress-stretch curves, it is demonstrated that both the hyperelasticity and the viscoelasticity in our PAAm hydrogel models are reflected. The scattered large deformation behaviors of three PAAm hydrogel models with the same water content indicate that the mesoscale conformation of polymer network dominates the mechanical behavior in large stretch. This is because the effective chains with different initial length ratio stretch to straight at different time. We further propose a stretch criterion to measure the fracture stretch of PAAm hydrogel using the fracture stretch of C-C bonds. Using the stretch criterion, the specific upper and lower limits of the fracture stretch are given for each PAAm hydrogel model. These fracture stretch ranges agree quite well with experimental results. The study shows that our coarse-grain PAAm hydrogel models can be applied to numerous single network hydrogel systems.